A CONCEPTUAL FRAMEWORK OF RELATIONSHIP BETWEEN LEADERSHIP STYLES AND EMPLOYEE PERFORMANCE THROUGH THE MODERATED MEDIATION OF ORGANIZATIONAL INNOVATION AND CULTURE - Srisakun , Chakrit; Intuluck, Watit (Dusit Thani College Journal, 2021)
This article aims to purpose the enriching employee performance through the moderated mediation of organizational innovation and culture based on the concept of leadership styles in service sector. Leadership styles performed the role to enhance the degree of organizational culture and organizational culture determined the role to support the employee’s performance. Furthermore, the organizational culture considered to mediate the relationship between leadership styles and employee’s performance, organizational innovation also performed the role of moderator variable to interact with leadership styles and organizational culture to encourage the degree of employee performance of service sector in Thailand. The conceptual of this framework will contribute to the concept of leadership theory and extend the boundary to explain how organizational culture and innovation interact with leadership styles and enhance the employee performance, to guide the establishment and manager to acknowledge the cause and effect among these variables in service sector based on context of Thailand. The result of intensive review on relevant literature found that the direct effect of leadership styles on organizational culture, and organizational culture on employee’s performance, the employee performance in service industry based on the context of Thailand may depends on setting the appropriately organizational culture and the degree of organizational culture to enhance the employee’s performance may depends on leadership styles. The leadership styles as the main sources to determine the organizational culture in service firm, and when consider the relationship between leadership style and employees performance mediate by organizational culture, the performance among the employees in service industry may increase as well.